(untitled) (Rudarsko-geološko-naftni zbornik, 2025)
A geopolymer is an unconventional inorganic binder prepared by an alkaline activator of alumina and silica-containing materials. This study has thoroughly evaluated the strength and durability performance of geopolymer mortars and represents a comprehensive attempt to highlight the advancement of environmentally conscious and innovative construction materials. The methodology used in this study includes X-ray diffraction (XRD), a scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), universal testing machines, and chemical methods (acid, sulfate, and chloride attack). The mechanical properties and durability of geopolymer mortars made at constant temperatures are evaluated and compared using different mineral additives. A comparative analysis of geopolymer mortar shows that M3 (fly ash) is an excellent choice for structural elements in construction projects where high strength and durability are paramount, as M3 (fly ash) has achieved the highest compressive (17.07 MPa) and flexural strengths (2.28 MPa) at all curing periods compared to M2 (RHA) and M1 (slag), which have intermediate (11.66 MPa, 2.17 MPa) and the lowest (10.10 MPa, 2.04 MPa) compressive and flexural strengths, respectively. In cases where acid resistance is a critical factor for construction, M1 appears to be the most suitable option, while M2 and M3 may require additional protective measures. M1, despite having slightly lower strength values than M2 and M3, demonstrates exceptional resistance to chloride attacks, making it a preferred option for projects in moderately chloride-rich environments. The compacted material increased strength and durability, while cracks, pores, and non-uniform particle arrangement reduced it. Overall, the abundance of minerals with elemental compositions such as Si, Al, O, and Na is responsible for the strong bonding for the cementation of geopolymer concrete. Therefore, keeping in mind the results of this study, different geopolymer mortars can be selected for construction purposes based on the demands of the projects.